Pharmacokinetic comparative study of tropoxine metabolite in miscellaneous animal species and humans - V. P. Zherdev; G. B. Kolyvanov; A. A. Litvin; P. O. Bochkov; R. V. Shevchenko; O. G. Grybakina; T. S. Ganshina (Фармакокинетика и Фармакодинамика)
Results of pharmacokinetic study of tropoxine metabolite (tropinone oxime; M-1) in experimental animals (rats, rabbits) and humans after administration several doses of tropoxine. Comparative analysis of the pharmacokinetic parameters characterizing of the metabolite formation intensity, i.e. Cmax of metabolite M-1 in the blood plasma increased in series: rats>humans> rabbits. Elimination rate of M-1 was decreased in series: rats>rabbits>humans